Examining Social Media Experiences and Attitudes Toward Technology-Based Interventions for Reducing Social Isolation Among LGBTQ Youth Living in Rural United States: An Online Qualitative Study - Escobar-Viera, César G.; Choukas-Bradley, Sophia; Sidani, Jaime; Maheux, Anne J.; Roberts, Savannah R.; Rollman, Bruce L. (Frontiers in Digital Health, 2022)
Purpose Lesbian, gay, bisexual, transgender, and queer (LGBTQ) youth living in rural areas who feel isolated are at high risk of depression and suicidality. Given the lack of support in their offline communities, many rural-living LGBTQ youth turn to social media for social support. In this qualitative study, we examined rural LGBTQ youth's social media experiences and attitudes toward technology-based interventions for reducing perceived isolation. Method In Spring 2020, we conducted online interviews with LGBTQ youth aged 14-19, living in rural areas of the United States, who screened positive for perceived social isolation (n = 20; 11 cisgender sexual minority, 9 transgender). Interviews examined (1) supportive social media experiences, (2) personal strategies to improve social media experiences, and (3) perspective on potential digital intervention delivery modalities. Data were analyzed using thematic analysis. Findings Related to supportive content and interactions, themes included (1) positive representation of and connecting with LGBTQ groups on social media are important; (2) content from people with shared experience feels supportive, and (3) lack of feedback to one's experiences is isolating. Regarding personal strategies to improve social media experiences, themes were (1) selecting platforms to connect with different audiences helps make for a more enjoyable social media experience, and (2) several social media platform features can help make for a safer social media experience. Youth discussed advantages and disadvantages of intervention delivery via a mobile app, social media pages or groups, conversational agents (chatbots), and a dedicated website. Conclusion Viewing positive representation of and connecting with LGBTQ groups, content from people shared experiences, and utilizing a wide array of platform features to increase the likelihood of positive connections are key to a positive social media experience among this group. Combining delivery modalities is key to engaging rural-living LGBTQ youth in digitally delivered support interventions to reduce perceived isolation. Our results inform future intervention research and conversations about social determinants of health between providers and rural LGBTQ patients.